2020
DOI: 10.1186/s40814-020-00677-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a clinical pharmacist team-based telehealth intervention in a rural clinic setting: a pilot study of feasibility, organizational perceptions, and return on investment

Abstract: Background Remote, centralized clinical pharmacist services provided by board-certified clinical pharmacists have been shown to effectively assist in chronic disease management. We assess the feasibility of implementing a pharmacist-led, remote, centralized pharmacy service to improve A1c levels in patient with diabetes in a rural clinic setting. Methods This was a non-randomized pilot and feasibility study. Participants were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Telehealth can reduce health care‐related costs associated with patients' lost wages, lost productivity, and travel time 6 . Telehealth facilitates more engaging and efficient management of chronic conditions and allows members of the patient care team, such as pharmacists to connect with patients and thereby improve patient outcomes 5,7‐9 . Telehealth interventions by pharmacists can improve the control of blood pressure and reduce serum levels of hemoglobin A1c when compared with the usual standard of care afforded by primary care providers alone 8,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Telehealth can reduce health care‐related costs associated with patients' lost wages, lost productivity, and travel time 6 . Telehealth facilitates more engaging and efficient management of chronic conditions and allows members of the patient care team, such as pharmacists to connect with patients and thereby improve patient outcomes 5,7‐9 . Telehealth interventions by pharmacists can improve the control of blood pressure and reduce serum levels of hemoglobin A1c when compared with the usual standard of care afforded by primary care providers alone 8,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 displays the study selection process. Five of the six studies were identified during the initial database search, [13][14][15][16][17] and the final study 18 was identified when hand-searching the reference list of a review article.…”
Section: Resultsmentioning
confidence: 99%
“…Studies over the past 10 years have highlighted multiple benefits of telehealth, two of the largest being increased patient access to care and improved patient outcomes. [1][2][3][4][5][6][7] With the advent of reimbursement expansion due to the pandemic, these advantages can now be applied to a diverse set of patients, not only those who reside in rural areas or areas with shortage of health care providers. This can lead to enhanced access to care and improved patient outcomes for both rural and urban residing patients and patients with other barriers to accessing care such as transportation or childcare difficulties.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%